MANAGEMENT OF DYSTOCIA DUE TO DOUBLE HEADED MONSTER IN A CROSSBRED JERSEY COW - NAG, B S PRADEEP; KALYAAN, U S; GOPIKRISHNAN, D; MANICKSUNDER, B; SATHIAMOORTHY, T; SARATH, T (The Indian Journal of Animal Reproduction, 2015)
Foetal anomalies or monsters occurs as a cause of dystocia in all the farm animals and is more commonin cows. Case of double headed monster found in crossbred cow is reported.
Keywords: Dystocia; anomalies; monster; cow